Komparatif Makna Simbolik Tari Topeng Malangan dari Indonesia dan Tari Biàn Liǎn dari Tiongkok - Nadia Ariellah Wahyu Amanda; Yang Nadia Miranti (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2026)
In these performing arts, masks serve as the main medium for expressing symbolic meaning, however these two mask arts show differences in symbolic interpretation, social function, and performance context. This research aims to analyze the comparison of the symbolic meaning of masks and social context in Malangan Mask Dance from Indonesia and Biàn Liǎn Dance from China. This study uses qualitative research to describe the approach of literary analysis using Clifford Geertz's interpretive anthropology framework and Victor Turner's symbolic theory. The results show that Malangan Mask Dance understands masks as symbols of stable characters with traditions, rituals, and social activities in Javanese society. Meanwhile, Biàn Liǎn Dance considers masks as symbols of transition, showing dramatic and rapid changes in emotions and characters. These differences reflect the cultural orientation, social structure, and interpretation by the supporting community of the symbolic function of performing arts in their social life. Keywords - Biàn Liǎn, Comparative, Malangan Mask Dance, Symbolic Meaning.